Mycotic aortic aneurysm as a postsurgical complication: report of a case and review of the literature - Donyad Farrokh; Fatemeh Sadeghi Ardakani; Farhad Yousefi; seyedeh Hanieh Afzalabadi (Journal of Cardio-Thoracic Medicine, 2019)
Mycotic aneurysms are localized and irreversible dilatations of the arteries caused by weakening and damaging the arterial wall by an invasive organism establishing infective arteritis. Mycotic aneurysm of the thoracic aorta is a rare event; however, it can be fatal if not diagnosed early or not treated appropriately. Clinical findings are usually nonspecific; however, contrast-enhanced computed tomography (CT) is a common imaging modality of choice for the detection of mycotic aneurysms. Current management consists of antibiotic therapy and surgical treatment or endovascular interventions as early as possible. Herein, we present a case report of mycotic aneurysm of the thoracic aorta as a postoperative complication in a 60-year-old female with a clinical history of the cardia and esophageal carcinoma who underwent thoracic surgery. The presence of mycotic aneurysm was detected after performing a contrast-enhanced thoracic CT scan